Can early serum lipase measurement be routinely implemented to rule out clinically significant pancreatic fistula after pancreaticoduodenectomy?. (September 2015) - Dalla Valle, Raffaele; De Bellis, Mario; Pedrazzi, Giuseppe; Lamecchi, Laura; Bianchi, Giorgio; Pellegrino, Carlo; Iaria, Maurizio
Abstract: Introduction: Postoperative pancreatic fistula (POPF) is the most significant cause of morbidity and mortality after pancreaticoduodenectomy (PD). We evaluated the role of postoperative serum lipase concentration in ruling out POPF in the immediate post-operative period. Materials and methods: We retrospectively analysed 98 consecutive PD performed between January 2009 and December 2014, investigating the correlation between postoperative day 1 (POD1) serum lipase concentration and POPF development. Results: 29 patients (29.5%) developed POPF [grade A, 17 (17.3%); grade B, 8 (8.1%); grade C, 4 (4%)]. A receiver operating characteristic (ROC) analysis was conducted to determine the threshold value of POD1 serum lipase associated with clinically significant POPF (AUC = 0.76, 95% CI 0.64–0.86, P = 0.01). Such threshold was ≤44.5 U/L and its sensitivity and specificity were 92% and 66%, respectively. The positive and negative predictive values (PPV, NPV) were 31% and 98%, respectively. Conclusion: Early routinely measurement of serum lipase proved to be helpful in ruling out clinically relevant POPF (CR-POPF). In our cohort, a POD1 cut-off of ≤44.5 U/L allowed early and accurate identification of patients with low probability to develop clinically significant POPF, who can eventually be selected for enhanced post-operative recovery with significant clinical and economic benefits.